Role of Fatty Liver Index and Metabolic Factors in the Prediction of Nonalcoholic Fatty Liver Disease in a Lean Population Receiving Health Checkup - Hsu, Chiao-Lin (Clin Transl Gastroenterol, 2019)
Some metabolic factors and noninvasive markers, including fatty liver index (FLI), are used to predict nonalcoholic fatty liver disease (NAFLD) in obese patients. Despite the increasing prevalence of NAFLD in lean patients (lean-NAFLD), the risk factors and predictors are not well determined in this population. We investigated factors associated with lean-NAFLD and validated their predictive ability. METHODS: From 9,293 examinees who underwent routine health checkups, we enrolled 4,000, aged ≥20 years, with a body mass index <24 kg/m(2) in our lean-NAFLD study population. NAFLD diagnoses were made according to the patients' histories, laboratory values, and sonographic criteria. Clinical variables, serum sugar, lipid, and liver profiles were evaluated using multiple logistic regression analysis. The predictive ability and optimal cutoff values for NAFLD were determined according to the area under the receiver operating characteristic curve. RESULTS: Overall, 18.5% (n = 740) of the lean population had NAFLD. Male sex, body mass index, body fat mass, fasting plasma glucose, uric acid, alanine aminotransferase, triglyceride, and FLI values were associated with NAFLD. FLI had the best discriminative ability to predict lean-NAFLD compared to the other biochemical markers. We further used the Youden index test and found an optimum cut-off value for FLI of 15 with the highest discriminant ability than other values. DISCUSSION: The prevalence of lean-NAFLD was not low. FLI was superior to other predictors including sex, liver function, and other metabolic factors, in the prediction of lean-NAFLD. FLI may be considered an easy to use, noninvasive marker to screen for lean-NAFLD.